Pd(ii)–NHC coordination-driven formation of water-soluble catalytically active single chain nanoparticles. Issue 23 (31st May 2018) - Lambert, Romain; Wirotius, Anne-Laure; Garmendia, Sofiem; Berto, Pierre; Vignolle, Joan; Taton, Daniel
Abstract : Intramolecular coordination of a linear copolymer precursor yields single chain nanoparticles (SCNP's) consisting of Pd(ii )-NHC2 crosslinks and showing a beneficial SCNP effect when used for the Suzuki coupling in water. Abstract : A well-defined linear statistical copolymer precursor, made of styrene, grafted poly(ethylene oxide) and benzimidazolium chloride units serving as N-heterocyclic carbene (NHC) ligand precursors, is designed by random RAFT copolymerization. Intramolecular coordination forming Pd(ii )–NHC2 crosslinks yields single chain nanoparticles (SCNPs). The formation of SCNPs is achieved by the insertion of Pd(OAc)2 into diluted solution, which is monitored by combined analyses, including NMR, SEC, DLS and TEM. When used for the Suzuki coupling in water, the catalytic activity of these Pd(ii )–NHC2 -containing SCNPs is greatly improved relative to Pd(OAc)2 as a benchmark molecular catalyst. When compared to a molecular catalyst of Pd–NHC2 -type, i.e. with a structure similar to that of the SCNP-supported catalytic units, the conversion to a reaction product is again higher, owing to a beneficial SCNP effect, although an increase in catalytic efficiency is not spectacular.